Uma análise fático-juridica do desastre do Rio Doce e o termo de transação e de ajustamento de conduta - Schimidt, Rafaella Boone (2019)
This dissertation explained the rupture of the Fundão dam, which occurred on November 5th, 2015, in Mariana County, state of Minas Gerais. He pointed the mining and capixabas localities affected by the iron mining tailings. It described the human, social, environmental, economic, material, health, psychological and spiritual harm caused. Adopted the term Rio Doce Disaster to refer to Fundão rupture and the injuries caused. He pointed out that the Rio Doce Disaster is still ongoing, as the damage to the Abrolhos Marine National Park was only confirmed in 2019. It presented the public civil actions filed by the Public Attorney and the Federal Prosecutor for containment, mitigation, compensation and reparation of the socio environmental and socioeconomic damages caused. He highlighted the establishment of the jurisdiction of the 12th Federal Court of the Judiciary Section of Minas Gerais for processing and judgment of these actions and other related. It explained the injunctions determined by said Court for the containment and repair of damages, as well as the interlocutory appeals filed in the face of the grant. He explained the Terms of Transaction and Adjustment of Conduct and the conciliation hearing held by the Conciliation System of the Federal Regional Court of the 1st Region for its judicial approval. He pointed out the problems diagnosed in the negotiation / conclusion and homologation processes of the Term and the decisions of the Superior Court of Justice and the 5th Panel of the Federal Regional Court of the 1st Region that declared the homologation sentence null and void. Analyzed some problems identified in the Terms of Transaction and Adjustment of Conduct from the perspective of the Brazilian Collective Civil Procedural Law. The primary objective of this paper was to analyze in fact and legally the Rio Doce Disaster, as well as to explain what the Transaction and Conduct Adjustment Term consisted of. Secondly, some of the problems of adjustment were examined from the perspective of Brazilian Collective Civil Procedural Law. The research conducted a case study, when it described and explained the disaster and still adopted the method of literature review. At the end, presented concluding notes. Due to a potential conflict of interest, the Union, the States of Minas Gerais and Espirito Santo and their organs could not be considered adequate to protect the lato sensu collective rights violated. Therefore, the positions of the Courts were correct in declaring the nullity of the homologation act of the adjustment. Although the legitimation in the Brazilian Collective Procedural Law derives from the law, with the legitimate asset being authorized to conduct the collective protection autonomously, the Courts are already beginning to appear to have a certain rigor regarding the participation of the lato sensu collective right holder group, all in view of appropriate debate and the way forward for the democratic construction of solutions. The Terms of Transaction and Adjustment of Conduct have substantial invalidity due to the non-concrete participation of groups holding lato sensu collective rights violated and counties affected by the Rio Doce Disaster.